Plasma levels of matrix metalloproteinase 9 in patients undergoing off-pump coronary artery bypass grafting - Li, Haiqing; Yuan, Zhize; Li, Sen; Qi, Quan; Liu, Jun; Zhou, Mi; Cai, Junfeng; Chen, Anqing; Wang, Zhe; Ye, Xiaofeng; Zhao, Qiang (Journal of Thoracic Disease, 2017)
Background: Matrix metalloproteinase 9 (MMP9) has recently emerged as a risk predictor in patients with cardiovascular diseases. However, little is known about the significance of increased plasma MMP9 in patients with perioperative myocardial injury. We aimed to investigate the role of MMP9 in the occurrence of myocardial injury during off-pump coronary artery bypass grafting (OPCAB). Methods: A total of 34 consecutive patients with coronary artery diseases (CAD) were recruited in this prospective, observational study. All patients were operated for OPCAB surgery. Serial blood samples were collected preoperatively and 12 hours after surgery. MMP9, together with cardiac troponin I (cTnI), creatinine kinase myocardial b fraction (CK-MB), C-reactive protein (CRP), and N-terminal pro B-type natriuretic peptide (NT-proBNP) levels in plasma were measured at each time-point. Results: MMP9 levels increased significantly at 12 hours after surgery, attaining nearly 2 times the baseline levels (P=0.0001). There was a significant correlation between preoperative (pre-OP) circulating levels of MMP9 and the left ventricular ejection fraction (LVEF) (r=0.48; P=0.004) as well as European System for Cardiac Operative Risk Evaluation (EuroSCORE) II (r=0.43; P=0.012). Patients were in New York Heart Association (NYHA) functional class III or IV heart failure showed a significantly higher MMP9 levels (1,348.0±337.2 vs. 630.4±93.0 ng/L, P=0.012) as compared to the patients in NYHA functional class I and II. No significant correlation was observed between MMP9 and age (P=0.612), serum creatinine (P=0.185), CRP (P=0.207), NT-proBNP (P=0.058). A significant correlation was observed in these data between the post-OP MMP9 and cTnI (r=0.35; P=0.003). Conclusions: Our study first established a connection between MMP9 and OPCAB procedure, suggesting that MMP9 could be a novel biomarker for identifying perioperative myocardial injury in patients undergoing OPCAB.